2017
DOI: 10.2525/ecb.55.71
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Supplemental Lighting on Growth and Medicinal Compounds of Japanese Honeysuckle (<I>Lonicera japonica</I> Thunb.)

Abstract: Japanese honeysuckle is an evergreen vine that grows naturally in Japan and East Asia. The buds and leaves of this plant are used as crude drugs known as Kinginka and Nindou, respectively, in Japan and East Asia. The medicinal compounds are chlorogenic acid and luteolin, which have antiviral, anticancer, anti-inflammatory, and antioxidant activities. The optimal environmental conditions for growing Japanese honeysuckle have remained unknown thus far. The aim of this study was to investigate the effects of supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In addition, the amount of bioactive compounds in red perilla decreases during both post-harvest drying and storage; therefore, the production of red perilla leaves with stable and high concentrations of bioactive compounds at harvest is needed. Hikosaka et al 2017 reported that greenhouse cultivation is an effective method for the steady production of medicinal plants because environmental conditions can be controlled to be suitable for plant growth and quality; furthermore, safer medicinal plants are produced with the use of fewer agrochemicals. Moreover, there is a possibility that the bioactive compound concentration in medicinal plants increases with environmental control in a greenhouse.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the amount of bioactive compounds in red perilla decreases during both post-harvest drying and storage; therefore, the production of red perilla leaves with stable and high concentrations of bioactive compounds at harvest is needed. Hikosaka et al 2017 reported that greenhouse cultivation is an effective method for the steady production of medicinal plants because environmental conditions can be controlled to be suitable for plant growth and quality; furthermore, safer medicinal plants are produced with the use of fewer agrochemicals. Moreover, there is a possibility that the bioactive compound concentration in medicinal plants increases with environmental control in a greenhouse.…”
Section: Introductionmentioning
confidence: 99%
“…For example, compared to control (20-20-20 fertilizer), when applying 15-10-30 and 10-30-20 fertilizer to green and red Perilla plants, respectively, TP and RA levels were remarkably and respectively increased without influencing plant growth. Hikosaka et al (2017) reported that greenhouse cultivation is an effective method for the steady production of medicinal plants because environmental conditions can be controlled for suitable plant growth and quality, so there is also the possibility that bioactive compound concentrations in medicinal plants can be increased under environmental control in greenhouses.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have revealed that the constitution and concentration of phenolic compounds and metabolites in medicinal plants, including Perilla, are largely influenced by various factors such as growth season, environment, light intensity or quality, cultivation methodology, phenological stage, nutrient level, and harvest time (Saeb and Gholamrezaee, 2012;Yoshimatsu, 2012;Chauhan et al, 2013;Selmar and Kleinwachter, 2013;Ha et al, 2012;Kiazolu et al, 2016;Lu et al, 2017;Kim et al, 2017;Umakanta and Oba, 2018). Moreover, Hikosaka et al (2017) reported that greenhouse cultivation is an effective method for the steady production of medicinal plants because environmental conditions can be controlled, and furthermore, safer medicinal plants are produced with the use of agrochemicals. Ogawa et al (2018) also demonstrated that bioactive compound 3 concentrations in red Perilla increased with nutrient solution temperatures in a greenhouse.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, quantifying the optimal stress level of a single environmental factor is crucial for the actual production of medicinal plants in a controlled environment. Hikosaka et al [45] reported that greenhouse cultivation is an effective method for the steady production of medicinal plants because lighting conditions can be suitably controlled for plant growth and quality, and it is possible that concentrations of bioactive compounds in medicinal plants can be increased through environmental control in a greenhouse.…”
Section: Influences Of Light Intensity Effects On Secondary Metabolitmentioning
confidence: 99%